Fecal transplantation from humans with obesity to mice drives a selective microbial signature without impacting behavioral and metabolic health - Neyrinck, Audrey M.; Ahmed, Hany; Leyrolle, Quentin; Leclercq, Sophie; Amadieu, Camille; Meuronen, Topi; Layé, Sophie; Cani, Patrice D.; Kärkkäinen, Olli; Bindels, Laure B.; Hanhineva, Kati; Delzenne, Nathalie M. (Springer Science and Business Media LLC, 2025)
Obesity is associated with alterations in the gut microbiome that may contribute to metabolic and mental health disturbances. Fecal microbiota transplantation (FMT) from humans to mice is a model proposed to study human microbiota-associated disorders. In this study, we investigated whether gut microbiota from human donors with obesity could affect behavior and metabolomic profiles of mice. Stools from donors with obesity and from lean donors were inoculated to antibiotic-pretreated mice fed a standard low-fat diet throughout the experiment. Obese-recipient mice exhibited a lower bacterial alpha-diversity and limited changes in specific taxa (e.g., an increase in Eubacterium) but were similar to lean-recipient mice in terms of dietary intake, body weight, fat mass, anxiety/depression-like behavior and glucose homeostasis. Non-targeted LC-MS metabolomic analysis revealed no change in the portal and cava serum samples. However, 1-methylnicotinamide, indole-3-acetic acid (I3A) and methyllysine were increased in the cecal content of obese-recipient compared to lean-recipient mice. Microbial metabolites derived from amino acids were positively correlated with Eubacterium. These results indicate that FMT from donors with obesity to mice fed chow diet (low in lipids) leads to minor but persistent change in intestinal microbial-derived metabolites, without recapitulating the metabolic and behavioral alterations of obesity.